Quantitatively Plotting the Human Face for Multivariate Data Visualisation Illustrated by Health Assessments Using Laboratory Parameters. (18th December 2013) - Hongwei, Wang; Hui, Liu
Abstract : Objective . The purpose of this study was to describe a new data visualisation system by plotting the human face to observe the comprehensive effects of multivariate data. Methods . The Graphics Device Interface (GDI+) in the Visual Studio.NET development platform was used to write a program that enables facial image parameters to be recorded, such as cropping and rotation, and can generate a new facial image according to Z values from sets of normal data (Z > 3 was still counted as 3). The measured clinical laboratory parameters related to health status were obtained from senile people, glaucoma patients, and fatty liver patients to illustrate the facial data visualisation system. Results . When the eyes, nose, and mouth were rotated around their own axes at the same angle, the deformation effects were similar. The deformation effects for any abnormality of the eyes, nose, or mouth should be slightly higher than those for simultaneous abnormalities. The facial changes in the populations with different health statuses were significant compared with a control population. Conclusions . The comprehensive effects of multivariate may not equal the sum of each variable. The 3Z facial data visualisation system can effectively distinguish people with poor health status from healthy people.